2022
DOI: 10.3390/jcm11123321
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PON1, PON2, PON3 and MPO Genes in Patients with Depressive Disorders

Abstract: Background: Taking into account the role of oxidative stress in neurodegeneration, we sought to evaluate the expression of genes for select enzymes with antioxidant properties (paraoxonases PON1, PON2 and PON3 and myeloperoxidase MPO) at the mRNA and protein levels in patients with depressive disorders. We further sought to determine the impact of oxidative stress in the etiopathogenesis of this group of mood disorders. Methods: A total of 290 subjects (190 depressed patients, 100 healthy controls) took part i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Paraoxonases (PON) are an enzyme family comprising of PON1, PON2, and PON3 that hydrolyze organophosphate chemicals [19][20][21]. PON1 is a plasmatic enzyme with paraoxonase and arylesterase (AREase) activity, as well as antioxidative and antiin ammatory effects [22][23]. PON1 is an HDL-associated protein that shields HDL and LDL cholesterol from oxidation and can hydrolyze oxidized LDL-cholesterol, which may have atheroprotective properties [24].…”
Section: Introductionmentioning
confidence: 99%
“…Paraoxonases (PON) are an enzyme family comprising of PON1, PON2, and PON3 that hydrolyze organophosphate chemicals [19][20][21]. PON1 is a plasmatic enzyme with paraoxonase and arylesterase (AREase) activity, as well as antioxidative and antiin ammatory effects [22][23]. PON1 is an HDL-associated protein that shields HDL and LDL cholesterol from oxidation and can hydrolyze oxidized LDL-cholesterol, which may have atheroprotective properties [24].…”
Section: Introductionmentioning
confidence: 99%
“…This study has limitations that are worth considering. First, based on studies that on one hand suggested that gene conversion may be an effective treatment for cerebral ischemia ( Driga et al, 2021 ), and on the other hand investigated PON1, PON2, PON3, and MPO gene expression in patients with depression ( Blizniewska-Kowalska et al, 2022 ), we considered that elderly patients with depression can also undergo genetic testing, which may provide information for the prediction of depression. In the future, it is worthwhile to collect a larger sample and add a gene marker project to explore the genetic characteristics of depression in the elderly and develop tools for its prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in a group of 190 depressed people and 100 healthy people showed that the expression of PON2 and PON3 genes at the protein level was significantly higher in patients with depression, while the mRNA expression of PON1, PON2, and PON3 genes did not differ in patients with depressive disorders compared to the control group. It was also shown that the expression of the MPO gene, both at the mRNA and protein levels, was significantly lower in patients with depressive disorders than in the control group [69].…”
Section: Inflammation In Depressive Disordersmentioning
confidence: 96%